Negative association between serum adropin and hypertensive disorders complicating pregnancy - Dong Lin; Jian Yong; Shuhua Ni; Weichao Ou; Xuerui Tan (Taylor & Francis Group, 2019)
Objective: Study the association of adropin and hypertensive disorders complicating pregnancy (HDCP). Methods: Patients with HDCP were matched with normotensive women (47 pairs). Adropin concentrations were detected by enzyme-linked immunosorbent assay. Results: Compared with the controls, the serum adropin levels were lower in the HDCP group (P < 0.001) and in HDCP subgroups (gestational hypertension, mild preeclampisa, and severe preeclampsia, term, preterm, early onset, and late onset) (all P < 0.05). After adjustment for confounders, adropin remained negatively associated with HDCP (P = 0.027). Conclusion: Lower adropin concentration is significantly associated with HDCP, suggesting that higher or normal adropin levels may be protective against HDCP.